The association between patient's compliance and age with the bonding failure of orthodontic brackets: a cross-sectional study - Isabela Vasconcelos Barbosa; Victor de Miranda Ladewig; Renata Rodrigues Almeida-Pedrin; Mauricio Almeida Cardoso; Joel Ferreira Santiago Junior; Ana Claudia de Castro Ferreira Conti (SpringerOpen, 2018)
Abstract Background An efficient orthodontic treatment must aim the best occlusal result in the shortest possible time. One of the factors that can interfere in this goal is the bracket debonding during the treatment. This study aimed at assessing the different factors related to brackets failure, highlighting age and patient cooperation with treatment. Methods The sample comprised 199 orthodontic patients of both genders (103 women and 96 men); divided into two groups-adolescents (12 to 18 years old, 118 patients) and adults (19 to 59 years old, 81 patients). A questionnaire was applied regarding the motivation of patients to seek treatment and whether they had received information on appliance care; patients also filled out their level of cooperation with treatment in a visual analog scale (VAS). Additionally, other variables were assessed, such as the teeth with bracket debonding, the presence of deep overbite, and the use of bite plate. The Mann-Whitney test was used, and a 5% significance level was applied for analyses. Results It was observed that 20.1% of patients presented at least one tooth with bracket failure, and the lower arch was the most prevalent site (47.5%). Adolescents presented more debonding (25.4%) than adults (12.3%). Individuals with better VAS scores on cooperation sought treatment on their own (p = 0.042), were adults (p ≤ 0.001), and showed lower rate of failure of brackets (p ≤ 0.001). The factors related to malocclusion and treatment performed had no statistical significance. Conclusion Greater cooperation was expected from adult individuals who sought treatment on their own and presented low rate of bracket failure.